Strategies of Implementing Multicultural Education: Insights from Bilingual Educators - Amirullah Abduh; Rosmaladewi Rosmaladewi; Martin Andrew (Universitas Negeri Makassar, 2023)
The purpose of this paper was to explore principals’ perceptions of their strategies to maintain their cultural and religious identities within a multicultural society.This multiple case studies of three institutions employed semi-structured interviews and documents. The research question guides this study: What are strategies that have been utilized within the institutions, to further the aims of multicultural education? The data in this study was analyzed thematically via NVivo Qualitative data analysis. The finding of this study showed that the institutions were committed to providing a public education alongside a multicultural education – respect for other religions, ethnicities, and cultures. These institutions have a strong commitment to their spiritual purpose and maintenance of their respective religious and cultural identities. The findings of this study have implications for the understanding of similar programs and the ways to preserve cultural and religious identities within educational contexts. Most studies of multicultural education have been conducted in public institutions resulting in little information on how ethnic institutions promote cultural and religious identities within their institutions and communities. This research contributes to the body of literature that examines the promotion of cultural and religious identities in ethnic institutions.